Are ABO Blood Groups or Rh Antigen Perinatal Factors Affecting the Pass Rate of Transient Otoacoustic Emissions Screening Tests in Healthy Newborns during the First 48 h of Life? - Jose Miguel Sequi-Canet; Jose Miguel Sequi-Sabater; Jose Ignacio Collar-Castillo; Nelson Orta-Sibu (MDPI AG, 2019)
Most hospitals recommend performing neonatal hearing screening. Transient evoked otoacoustic emission (TEOAE) tests represent an ideal technique for conducting this process. Previous studies have related the influence of ABO blood group and Rhesus antigens (Rh) on the susceptibility to various pathologies. However, available data about the potential relationship between ABO blood groups, Rh, and TEOAE pass rates are sparse. Recently, several authors concluded that O blood group and Rh+ are possible influential factors of TEOAE pass rates. Significantly different TEOAE amplitude response between the four main ABO blood groups were observed among normal-hearing individuals. Moreover, ABO blood groups were discussed as a possible influential factor for the development of noise-induced hearing loss later in life. The aim of this study was to investigate the relationship between ABO blood groups, Rh, and the first TEOAE pass rates in healthy newborns. Data were retrospectively collected from healthy newborns at the maternity ward of F. Borja hospital in Gandia (Spain). Rh and ABO were compared with the results of TEOAE performed within the first 48 h of life. Results: the study group included 2765 newborns. No significant correlation between ABO blood group or Rh and TEOAE pass rates was observed in comparative tables. Conclusion: ABO blood group and Rhesus antigens do not appear to have a significant impact on the pass rate of TEOAE screening in healthy newborns.